Antecedents the use of social commerce in small medium enterprise: A conceptual framework - Sutomo, Erwin; Nur Shamsiah, Abdul Rahman; Awanis, Romli (IEEE, 2021)
SMEs need to pay attention to several factors so that customers and SMEs can continue to use S-Commerce. The obstacle faced by SMEs is that they cannot consistently use S-Commerce. This study aims to produce a proposed conceptual framework to see the relationship between factors for using S-Commerce in SMEs. The proposed framework has developed through the literature related to using social commerce in SMEs, including the relationship between determinant factors using S-Commerce in SMEs. The reviews are viewing from technological, organizational, social factors, including customer and competitor factors. The results of this study indicate that 11 factors determine the use of S-Commerce in SMEs. The social connectedness and trust factors are some of the determining factors in using S-Commerce. The resulting proposed conceptual framework contributes to a better understanding of the considerations for using S-Commerce in SMEs, especially for SME business owners.